Pandangan Islam terhadap Etika Kecerdasan Buatan (Artificial Intellgence) dalam kehidupan sehari-hari - Arya Farlan Ananda; Suci Nurhidayah; Muhamad Zahirianata; Naila Sa’adah (Indo Publishing, 2025)
The advancement of artificial intelligence (AI) technology has had a significant impact on many parts of daily life, particularly for Muslims. The rise of problems about the ethics of employing AI from an Islamic perspective is worth discussing. This essay will look at Islamic perspectives on AI and how Islamic ethics might help guide the usage of this technology. This study takes a qualitative approach, employing literature study methods and an analysis of Islamic literature on ethics, technology, and artificial intelligence. The conclusion demonstrates that Islam supports the use of technology that benefits humanity while prioritizing ethical concepts such as justice, responsibility, and prudence in coping with the potential negative consequences of AI.